STUDENTS’ PERCEPTIONS ON WATTPAD IN READING IN ENGLISH DEPARTMENT UNIVERSITAS BANDAR LAMPUNG - Rodiatun Rodiatun; Harpain Harpain (Universitas Bandar Lampung, 2020)
In the development of technology, reading can be obtained both from books and other media like handysmartphones. One application that can be used as a reading source, social and entertainment medium atonce is Wattpad application since Wattpad is not only as simple as reading platform but it also facilitatesthe readers to directly connect with other readers and their favorite writers. Wattpad may encourage thetaste of reading especially extensive reading or reading for pleasure. Therefore, Wattpad ismultifunctional medium that may enhance educational performance, social engagement, and personaldevelopment. This research aimed to explore the students’ perception on Wattpad in reading. The sampleof this research was all students of English Department of Universitas Bandar Lampung who usedWattpad as the reading platform. They are from first until thirteenth semester. This research appliedqualitative design with descriptive qualitative method. The data were collected through two instruments:questionnaire and interview. The result indicated that most students have positive perceptions on Wattpadin reading especially in enhancing their vocabulary.